Anxiety Levels Among Elderly With Comorbidities: A Descriptive Study In Ujung Tibu Village - Rafqia, Alifa; Suharto, Dewi Nurviana; Manggasa, Dafrosia Darmi; Langitan, Rosamey Elleke (Madago Nursing Journal, 2025)
Background: The elderly with comorbidities are vulnerable to psychological problems such as anxiety, which can worsen their health and reduce their quality of life. This study aimed to describe the anxiety levels and demographic characteristics of elderly individuals with comorbidities in Ujung Tibu Village. Methods: This study used a descriptive design with a cross-sectional approach. A sample of 37 elderly people who met the inclusion criteria was selected via purposive sampling. Anxiety levels were measured using the Geriatric Anxiety Scale (GAS) questionnaire. Data were analyzed using descriptive statistics and presented as frequency distributions and percentages. Results: Most respondents experienced mild anxiety (73.0%), followed by moderate anxiety (21.6%), and severe anxiety (5.4%). The dominant demographic characteristics were female (78.4%), married (64.9%), living with their husband (45.9%), having a illness duration of 1-5 years (70.3%), and suffering from hypertension (64.9%). Conclusion: The anxiety level of elderly people with comorbidities in Ujung Tibu Village is predominantly mild. Community activities like the Integrated Health Post (Posyandu) and family support are suspected to be protective factors. Focused nursing interventions are recommended for the minority experiencing moderate to severe anxiety